Pengaruh Citra Toko Dan Kepercayaan Toko Terhadap Loyalitas Konsumen Pada Toko Station Game Di Tenggarong - Rahmat Ramadhani; Iskandar Iskandar; Awang Yacoub Luthman (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
Abstract :Toko Station Game Tenggarong which is a branch of Station Celular Samarinda which serves the sale and purchase of mobile phones and accessories that are located on the lake Semayang RT.12 Kelurahan Melayu Tenggarong District. The goods are sold at Tenggarong Station Station Shop directly imported from jakarta and surabaya. The purpose of this study is to find out whether the variables of Store Image and Store Trust affect simultaneously to Consumer Loyalty At Station Station Game In Tenggarong, to find out, Are the variables of Store Image and Store Trust partially influence on Consumer Loyalty At Station Station Game Di Tenggarong and to know, Among the independent variables are the variables which have the most dominant influence on the Consumer Loyalty At Station Stores Game In Tenggarong? From both result of partial correlation test above seen value of Scitra variable of store bigger influence than store trust variable, so store image variable is the most dominant variable influence to consumer loyalty. From the description, it can be concluded that the second hypothesis in this study